Effects of Sports on Social and Cultural Transformations - Violeta Šiljak; Saša Vajić; Goran Zbiljić (Ukrainian Policymaker)
Today, sport represents a social phenomenon that first of all represents the achievement of certain goals that have a primarily human character based on preserving and strengthening health, improving physical abilities and accomplishing many tasks necessary to improve the quality of human life. In conjunction with other social values (culture, education, science, etc.), it has become one of the primary human activities. Through sports activities (preparation, organization, implementation, participation, etc.), people develop team spirit, solidarity, tolerance, strengthen communication and thus contribute to personal development and the achievement of their goals.We should not ignore the threats and challenges that sport is particularly facing today, such as: doping, racism, violence in sport, political interference in sport, corruption and other «diseases» of modern society, to which sport is exposed and where there is constant fight with the aim of turning sport to its own goals based on humane values. Sport connects people, crosses the boundaries of language, religion and nation and often serves as a platform for social change and political statement. Also, sporting successes can be a source of inspiration and motivation, showing the strength of the human spirit in facing challenges. Bearing in mind that the subject of this research is the impact of sport on social and cultural changes, the goal of the research was defined, which refers to determining the social and cultural significance of sport. In this paper, it was critically studied how sport reflects the culture and traditions of different countries, how it contributes to social movements and changes, and how sports successes can serve as motivation for overcoming life’s challenges. Through examples from different parts of the world, the complex relationship between sport and life and how it shapes and empowers individuals and communities is looked at.